Two Decades Without the Mediterranean Monk Seal in the Al Hoceima Marine Protected Area: Habitat Suitability Assessment and Monitoring Insights - KARIM, Souhail; BOUAZZATI, Hasna; CHERKAOUI DEKKAKI, Hinde (Research in Ecology, 2025)
The Mediterranean monk seal (Monachus monachus) is an endangered pinniped species historically distributed along the Moroccan Mediterranean coast. Despite confirmed historical presence in the Al Hoceima region, no sightings have been recorded for over two decades. Between 2024 and 2025, a coastal habitat monitoring campaign was conducted within the Al Hoceima Marine Protected Area (MPA) to assess the structural availability and oceanographic suitability of haul-out caves for potential monk seal recolonization. A total of 15 sea caves were surveyed along a 40 km segment of coastline, using geospatial mapping, geomorphological characterization, and swell exposure assessment. Caves were classified into three suitability categories based on morphological depth, elevation of resting platforms above tidal influence, exposure to prevailing hydrodynamic conditions, and degree of anthropogenic disturbance. Three caves (Category A) were identified as highly suitable, exhibiting deep, sheltered configurations with minimal swell penetration and structurally stable platforms above mean sea level. Eight infrared camera traps were deployed in selected high-potential caves to monitor biological and human activity. Although no monk seals were detected ( 240 camera-days), the study confirmed the integrity of several key marine cavities and highlighted episodic human presence, including artisanal fishing and ecotourism. These findings provide a critical geospatial and structural baseline for marine habitat monitoring in the region and emphasize the relevance of integrating coastal morphology, marine dynamics, and spatial protection in future monitoring frameworks. The results support adaptive management strategies and inform oceanographic approaches to habitat restoration and species recovery in semi-enclosed Mediterranean systems.